A Questionnaire on Relative Deprivation of University Students and Its Application in Measuring Mental Health - Jia, Liuzhan (Frontiers in Psychology, 2022)
Objective Relative deprivation is associated with collective and individual variables in psychology. However, so far, there are few studies on measuring the relative deprivation of university students. Therefore, this study designs the University Students’ Relative Deprivation Questionnaire (USRDQ), verifies its validity and reliability, and then uses it to measure the mental health of students. Methods After reviewing the relevant studies and conducting a theoretical analysis and an open questionnaire survey, this article determined the structural dimension of USRDQ. A total of 103 university students were selected to take the open questionnaire survey, 200 were selected to engage in the item analysis, exploratory factor analysis, and internal consistency reliability test, 257 were selected to engage in the confirmatory factor analysis, and 287 were selected to take the retest reliability. Results The USRDQ includes 19 items under the three dimensions, namely, social comparison, cognitive evaluation, and emotional experience. Factor loads range from 0.49 to 0.87, which accounted for 63.39% of the total variation. The questionnaire has good fitting indicators (χ2/df = 2.64, NFI = 0.89, CFI = 0.93, GFI = 0.91, RMSEA = 0.08). The Cronbach’s α coefficient of the questionnaire is 0.916, and the coefficients of the three factors range from 0.805 to 0.934. The results of the survey show that the relative deprivation of students is quite high with a mean of 76.78 and a standard deviation of 16.96.